THE BRITISH SCORCHED EARTH AND CONCENTRATION CAMP POLICIES IN THE POTCHEFSTROOM REGION, 1899–1902 - Van den Bergh, G.N. (Scientia Militaria - South African Journal of Military Studies, 2012)
The continued military resistance of the Republics after the occupation of Bloemfontein and Pretoria and exaggerated by the advent of guerrilla tactics frustrated the British High Command. In the case of the Potchefstroom region, British aggravation came to focus on the successful resurgence of the Potchefstroom Commando, under Gen. Petrus Liebenberg, swelled by surrendered burghers from the Gatsrand again taking up arms. A succession of proclamations of increasing severity were directed at civilians for lending support to commandos had no effect on either the growth or success of Liebenberg’s commando. His basis for operations was the Gatsrand from where he disrupted British supply communications. He was involved in British evacuations of the town in July and August 1900 and in assisting De Wet in escaping British pursuit in August 1900. British policy came to revolve around denying Liebenberg use of the abundant food supplies in the Gatsrand by applying a scorched earth policy there and in the adjacent Mooi River basin. This occurred in conjuncture with the brief second and permanent third occupation of Potchefstroom. The subsequent establishment of garrisons there gave rise to the systematic destruction of the Gatsrand agricultural infrastructure. To deny further use of the region by commandos it was depopulated. In consequence, the first and largest concentration camp in the Transvaal was established in Potchefstroom. The policies succeeded in dispelling Liebenberg from the region.